Identifikasi Perilaku Seksual Menyimpang Pada Narapidana di Lembaga Pemasyarakatan - Mohamad Ridho Pijar Gemilang; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Prisoner or correctional inmate is a law violator who has received a final decision from the court and is then placed in a correctional institution to serve his criminal sentence. Imprisonment for law violators will deprive a person of their right to freedom and independence. Not only focusing on that, imprisonment is intended so that prisoners receive guidance so they can realize their mistakes and change into better humans. However, in implementing coaching in prisons, various obstacles are still found, such as overcrowded prison conditions. This condition can trigger other problems in prison if not treated immediately, one of which is the emergence of deviant sexual behavior in prisoners. Sex is one of the basic human needs that must be fulfilled and otherwise it will cause the prisoners to engage in abnormal sexual behavior to fulfill their desires. Deviant sexual behavior is any behavior that is driven by desire with the opposite sex or with the same sex, often even using unnatural sex objects. Sexual deviation occurs when an individual carries out activities to obtain pleasure through relationships outside of heterosexual sexual relations. The aim of this research is to find out what factors cause the emergence of sexual deviant behavior in prisoners and what efforts can be made to minimize and anticipate sexual deviant behavior in correctional institutions.